2012
DOI: 10.1186/1471-2261-12-3
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity vs general obesity for identifying arterial stiffness, subclinical atherosclerosis and wave reflection in healthy, diabetics and hypertensive

Abstract: BackgroundOur aim was to analyze the relationship between abdominal obesity and general obesity, with subclinical atherosclerosis, arterial stiffness and wave reflection in healthy, diabetics and hypertensive subjects.MethodsA cross-sectional descriptive study was made of 305 individuals (diabetics 32.8%, hypertensive subjects 37.0% and healthy individuals 30.2%). Measurements: Body mass index (BMI), waist circumference (WC), body fat percentage (BFP) and waist/height ratio (WHtR). Arterial stiffness was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
79
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 38 publications
10
79
0
7
Order By: Relevance
“…Accumulation of fat tissue, especially in the abdominal region, predisposes to a series of risk factors through a highly frequent association with outcomes that favor the occurrence of cardiometabolic disorders 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of fat tissue, especially in the abdominal region, predisposes to a series of risk factors through a highly frequent association with outcomes that favor the occurrence of cardiometabolic disorders 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…In adults, a positive relationship between obesity and PWV has been described in cross-sectional studies, 22,23 and a reduction in PWV was observed after losing weight, 24 although these studies had not considered the impact of BP values at the same time. Controversial results exist in the childhood population 14,25,26 that may be partially explained by differences in patient populations (age, sex, and small sample size) and heterogeneity of the techniques used.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [33] found that abdominal obesity by itself is an independent marker of subclinical atherosclerosis in women. In other studies, abdominal obesity was also associated with arterial stiffness [34] and an increase in carotid intima media thickness [34,35]. Konishi et al [36] showed that the visceral fat area is associated with carotid artery plaque formation in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%